Utilização de magnetorresistores no desenvolvimento de novas técnicas para aplicações em gastroenterologia - Paixão, Fabiano Carlos [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Biomagnetic techniques have been employed successfully to study gastrointestinal (GI) tract. They are enable to measure the magnetic field of magnetized markers, the markers and tracers responses to applied magnetic field excitation, and the magnetic field occurred by GI electrical activity. This work presents some instrumentation developed to evaluate different parameters of GI tract. The equipment built uses anisotropic magnetoresistive (AMR) sensor to measure magnetic field and true rms-to-dc voltage converter in order to reduce the cost of techniques that employ alternate (AC) magnetic excitation. In this work were developed: a magnetic method for localization of enteral feeding tube, a solution to replace lock-in amplifier for true rms converter, an instrumentation using AMR sensor (one axis-sensing) to evaluate the pharyngeal transit time, another instrumentation using AMR sensor (three axis-sensing) to evaluate esophageal transit time and finally, a equipment consisted of 36 AMR sensors to evaluate the gastric motor activity from rats and in order to obtain magnetic images from different kinds of phantoms. All equipments were tested and showed sensitivity to be employed in GI studies. The equipments developed are low cost, radiation free, portable and enable to applications in gastroenterology, pharmacology, pharmaceutical and medical clinic.

As técnicas biomagnéticas vêm sendo empregadas com sucesso no estudo do trato gastrintestinal (TGI). Elas podem medir o campo magnético originado pela atividade elétrica dos órgãos, o campo de marcadores magnetizados ou a resposta de marcadores ou traçadores a um campo magnético de excitação. Este trabalho apresenta uma coletânea de instrumentações desenvolvidas para aplicações no trato gastrintestinal. Os equipamentos desenvolvidos utilizaram sensor anisotrópico magnetorresistivo (AMR) para medir campo magnético e conversores de tensão true rms-to-dc objetivando a redução de custo das técnicas que empregam excitação magnética alternada (AC). Foram desenvolvidos um método de localização magnética de sonda nasoenteral, uma solução para substituição dos amplificadores lock-in’s por conversores true rms, uma instrumentação com sensor AMR com um eixo de detecção para avaliar o trânsito faringiano, uma instrumentação com sensor AMR com três eixos de detecção para avaliar o trânsito esofagiano e uma instrumentação com 36 sensores que foi aplicada para obter imagens magnéticas de diferentes fantomas e para avaliar a atividade de contração gástrica em um modelo in vivo – ratos. As instrumentações foram avaliadas em testes in vitro e in vivo e apresentaram sensibilidade para o emprego no trato gastrintestinal. Os equipamentos desenvolvidos são de baixo custo, livre de radiação ionizante, portáteis e que possibilitam aplicações em gastroenterologia, farmacologia, farmacotécnica e na clínica médica.
Keywords: Fisica medica; Gastroenterologia - Diagnóstico - Técnicas; Biomagnetismo; Enteral feeding tube